2015
DOI: 10.1039/c5ta07970e
|View full text |Cite
|
Sign up to set email alerts
|

An adaptive supramolecular organic framework for highly efficient separation of uranium via an in situ induced fit mechanism

Abstract: The as-synthesized adaptive supramolecular organic framework (MA–TMA) filled with abundant hydrogen-bonded N-/N and N-/O-heterocyclic motifs exhibits remarkable ability for highly efficient separation of uranium via an in situ “induced-fit” ion recognition mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(42 citation statements)
references
References 58 publications
(47 reference statements)
3
38
0
1
Order By: Relevance
“…After U­(VI) adsorption, the peak related to the CN– O H produced a shift of 0.16 eV (Figure d), indicating that U­(VI) can interact with the CN– O H groups. On the whole, the peaks of mGO-PAO became wider and shifted to higher binding energy after adsorption of U­(VI), which is consistent with the result reported in the literature. , …”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…After U­(VI) adsorption, the peak related to the CN– O H produced a shift of 0.16 eV (Figure d), indicating that U­(VI) can interact with the CN– O H groups. On the whole, the peaks of mGO-PAO became wider and shifted to higher binding energy after adsorption of U­(VI), which is consistent with the result reported in the literature. , …”
Section: Resultssupporting
confidence: 91%
“…On the whole, the peaks of mGO-PAO became wider and shifted to higher binding energy after adsorption of U(VI), which is consistent with the result reported in the literature. 55,56 On the basis of the XPS analysis, it can be concluded that the U(VI) was adsorbed onto mGO-PAO through the complexation of U(VI) with the imine and the hydroxyl, which probably is due to the η 2 chelation, 57,58 as shown in Figure 14. The results of XPS analysis also indicated the successful preparation of mGO-PAO.…”
Section: Effect Of Temperature and Thermodynamicmentioning
confidence: 97%
“…That picture is changing; a range of porous hydrogen-bonded organic frameworks (HOFs) 74 —also referred to as supramolecular organic frameworks (SOFs) 75 —has now been reported. 30 , 68 , 74 93 The most porous of these so far are Mastalerz’s triptycene benzimidazolone and analogues, 30 , 68 but multiple properties have been studied in addition to surface area, such as fullerene capture, 76 uranium capture, 86 fluorocarbon capture, 94 ion absorption, 89 proton conduction, 78 thermoelasticity, 79 sensing, 81 , 84 , 87 enantioseparations, 91 CO 2 separation, 78 , 80 , 82 , 85 , 90 , 95 and hydrocarbon separation. 68 , 74 , 92 This is a rapidly developing area, and solution processability is a potential advantage for HOFs and SOFs, too.…”
Section: Porous Molecular Crystalsmentioning
confidence: 99%
“…Uranium is essential for the sustainable development of the nuclear industry, [1][2][3] the uranium content in the ocean (about 4.5 billion tons) is almost 1000 times that of uranium on land. 4,5 To achieve continuous development of nuclear energy and environmental protection, it is of considerable significance to develop effective technology for extracting uranium from natural seawater.…”
Section: Introductionmentioning
confidence: 99%